Management consulting : a guide to the profession - Kubr, Milan (International Labour Office, 2002)
This is a widely recognized reference work on the state of the art of management consulting. It offers an extensive introduction to consulting: its nature, professional standards, intervention methods, behavioural rules, current developments and future perspectives.
Keywords: Business consultants.; Consultants; Conseillers d'entreprise.; REFERENCE -- Questions & Answers.; BUSINESS & ECONOMICS -- Consulting.; Business consultants; Organisatieadvisering.; Conseil en gestion.; Formation (Éducation); Gestion.; Perfectionnement.; Société de conseil.; Guide (Descripteur de forme)